Spiritualitas Budaya Jawa dalam Seni Tari Klasik Gaya Surakarta - Silvester Pamardi; Timbul Haryono; R.M. Soedarsono -; A.M. Hermien Kusmayati (LP2M ISBI Bandung, 2014)
ABSTRACT Javanese classical dance has grown dynamically in line with the history of the palaces in Central Java, especially after the fifteenth century that began in the era of the kingdom of Demak. It has lived and thrived in the court of Mataram Islam since the period of Panembahan Senapati at Kotagede, the time of Sultan Agung in the palace Plered, until the moving of the palace of Mataram to Kartasura.This research methods is focused on the use of qualitative data with the questions of ‘why’ and ‘how’ to unravel the mystery behind of the phenomenon. This actions are carried out with approach of multi- disciplinary such as science of history, social science, and choreography.The events of Gianti agreement in 1755 did not give only influence and impact on the power of the king of Mataram to had to be split into two regions, namely the region of Surakarta and Yogyakarta Sul- tanate region, but also had implications to the life of Javanese culture. The culture of Javanese which was originally derived from the one kingdom, namely Mataram Kasunanan, then divided into two styles, namely Javanese culture of Surakarta and Yogyakarta. Fortunately, in the palace of Kasunanan Surakarta as well as in the Kasultanan Yogyakarta palace is still being developed classical Javanese arts based on cultural and adiluhung values; respectivelly developed in the diﬀerent patterns or styles. The values of spiritual ‘Javanese’ is remained as a source of reference. Keywords: the art of dance, classical, spirituality of Javanese ABSTRAK Seni tari klasik Jawa telah berkembang secara dinamis seiring dengan sejarah perkembang- an keraton-keraton di Jawa Tengah, terutama setelah abad XV yang dimulai pada era kerajaan Demak. Seni tari klasik Jawa hidup dan berkembang di lingkungan istana Mataram Islam sejak periode Panembahan Senapati di Kotagede, atau jaman Sultan Agung di keraton Plered sampai dengan berpindahnya keraton Mataram ke Kartasura.Metode penelitian ini konsentrasi utamanya pada penggunaan data kualitatif dengan per- tanyaan-pertanyaan ’mengapa’ dan ’bagaimana’ untuk mengungkap misteri yang berada di belakang fenomena yang ada. Tindakannya dilakukan dengan pendekatan multi disiplin dari ilmu-ilmu sejarah, sosial, dan koreografi.Peristiwa perjanjian Gianti pada tahun 1755 tidak saja berpengaruh dan berdampak pada kekuasaan raja Mataram yang harus membagi menjadi dua wilayah, yaitu wilayah Kasunanan Surakarta dan wilayah Kasultanan Yogyakarta, tetapi juga berimplikasi pada kehidupan ke- budayaan Jawa. Kebudayaan Jawa yang semula bersumber dari satu kerajaan, yaitu Mataram Kasunanan, kemudian menjadi dua corak, yaitu kebudayaan Jawa Surakarta dan Yogyakarta. Namun demikian, baik di istana Kasunanan Surakarta maupun istana Kasultanan Yogyakarta tetap mengembangkan kesenian klasik Jawa berdasarkan nilai-nilai budaya adiluhung walau- pun dalam corak atau gaya yang berbeda. Nilai-nilai spiritualitas ‘kejawen’ tetap menjadi sum- ber acuannya. Kata kunci: seni tari, klasik, spiritualitas Jawa